The diatom genus Hantzschia (Bacillariophyta) in Xinjiang Province, China - You, Qingmin; Kociolek, John Patrick; Wang, Quanxi (Phytotaxa, 2015)
Hantzschia species are uncommon in Xinjiang Province, usually found in small populations and found only in a few samples. However, the diversity in the region is relatively high, with 13 species and 1 variety being identified. Except for the cosmopolitan species H. amphioxys, H. abundans, H. virgata and H. distinctepunctata, most of the taxa in Hantzschia observed in this region have limited distributions, including H. vivacior, H. nitzschioides, H. compacta, H. barckhausenii, H. longa and H. vivax, as well as the species described herein as new. Four new species of Hantzschia are described: H. pseudobardii, H. sinensis, H. yili and H. subrobusta, a further two interesting species, H. vivacior and H. nitzschioides are documented with light and scanning electron microscopy. All species described are compared with other similar Hantzschia taxa from other localities or compared to holotype specimens. These data show a higher diversity of diatoms in Xinjiang Province than previously understood and provide additional information for understanding their biogeography.